1990
DOI: 10.1111/j.1432-1033.1990.tb19287.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane topography of the subunits of ubiquinol – cytochrome‐c oxidoreductase of Saccharomyces cerevisiae

Abstract: The topology of the subunits of ubiquinol–cytochrome‐c oxidoreductase of the yeast Saccharomyces cerevisiae has been determined using a digitonin/proteinase K assay. With this assay we were able selectively to disrupt the mitochondrial membranes and to identify the subunits which became proteinase‐K‐sensitive after disruption of either the outer or both outer and inner membranes. This approach confirmed previous indications for the localization of the core I protein, cytochrome c1, cytochrome b, the FeS protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Triton X-100 solubilizes all membranes and therefore makes all proteins accessible for proteinase K. Panel C shows results obtained for mitochondrial proteins facing either the matrix (FI~) or the IMS (ISP42). Panel A shows the localisation of subunits VII and VIII as was determined before [9]. Resistance to proteinase K of the 14-kDa subunit VII (lane 5) shows that this protein is not exposed to the IMS, consistent with earlier findings which indicated that this protein faces the mitochondrial matrix [9].…”
Section: Localisation Of the N-terminus Of Subunit VIIIsupporting
confidence: 84%
See 4 more Smart Citations
“…Triton X-100 solubilizes all membranes and therefore makes all proteins accessible for proteinase K. Panel C shows results obtained for mitochondrial proteins facing either the matrix (FI~) or the IMS (ISP42). Panel A shows the localisation of subunits VII and VIII as was determined before [9]. Resistance to proteinase K of the 14-kDa subunit VII (lane 5) shows that this protein is not exposed to the IMS, consistent with earlier findings which indicated that this protein faces the mitochondrial matrix [9].…”
Section: Localisation Of the N-terminus Of Subunit VIIIsupporting
confidence: 84%
“…This subunit was shown to be located at the matrix side of the inner membrane [9]. In yeast this pro- Mitochondria were treated as described in Section 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations